THE DIFFICULTIES ENCOUNTERED BY NON-ENGLISH DEPARTMENT STUDENT IN SPEAKING ENGLISH AT MADAKO UNIVERSITY - Jaya, Jaya (Jurnal Madako Education, 2021)
The aimed of this research was to investigate the difficulties encountered by non-English department student at second semester of Madako University and the factors trigger in speaking English at second semester of Madako University. The design of this research was a qualitative research. The research samples were consisted of 15 students at A Class of 2th semester, which used purposive sampling. The data obtained from questionnaires and interviews. The data were analyzed through some steps among data reduction, data display and conclusion drawing. From the data analysis, the researcher found some conclusion of students’ difficulties was lack of confidence from (50%), afraid of making mistake (60%), and less of English ability (67%) and the result of interview that researcher found the difficulties are vocabulary and pronunciation. The results of interview in internal factor that the researcher found are Interest, Intelligence, shy and nervous. Based on the data above the result of interview in external factor that found by researcher is student environment or classroom environment that is from Family and Lecturer